Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.jtcvs.2017.10.152
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation as a direct bridge to heart transplantation in adults

Abstract: Bridge to transplant with ECMO was associated with increased early/mid-term mortality, especially in patients with a high MELD-XI score who demonstrated > 50% 3-year mortality. These findings may help to inform future organ allocation policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
122
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(129 citation statements)
references
References 17 publications
6
122
0
1
Order By: Relevance
“…These findings support previous studies that have demonstrated the prognostic utility of MELD‐XI in predicting outcomes for patients supported with VA‐ECMO as a bridge to transplant 26,28 . Sern Lim 28 found remarkably similar results in a cohort of 26 patients undergoing VA‐ECMO as bridge to transplantation; 69% mortality for patients with a baseline MELD‐XI of 14 or greater compared to 31% for those with a baseline MELD‐XI less than 14.…”
Section: Resultssupporting
confidence: 87%
“…These findings support previous studies that have demonstrated the prognostic utility of MELD‐XI in predicting outcomes for patients supported with VA‐ECMO as a bridge to transplant 26,28 . Sern Lim 28 found remarkably similar results in a cohort of 26 patients undergoing VA‐ECMO as bridge to transplantation; 69% mortality for patients with a baseline MELD‐XI of 14 or greater compared to 31% for those with a baseline MELD‐XI less than 14.…”
Section: Resultssupporting
confidence: 87%
“…The combination of the recent prioritization of patients on TMCS and reports of ECMO BTT mortality exceeding 30% at 1-year follow-up has made Impella 5.0 an attractive device option for direct bridge to OHT. 1,3,7 Furthermore, bridging patients in refractory cardiogenic shock with Impella 5.0 provides excellent hemodynamic support with the potential for reversal of end-organ dysfunction while waitlisted for OHT. 11 The risk of device-failure and device-related complications with prolonged Impella 5.0 support is not uncommon and often necessitates either cardiac recovery or a bridge to a CF-LVAD or OHT.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in outcomes of continuous-flow left ventricular assist devices (CF-LVAD) over the last several years led many to question whether patients supported with CF-LVAD should be less prioritized on the heart transplant waiting list. [1][2][3] Indeed, patients with CF-LVADs have historically superior waitlist survival and rates of transplantation when compared to patients supported with temporary mechanical circulatory support (TMCS). 4,5 The surmounting evidence that CF-LVAD and TMCS outcomes were discrepant was addressed during the adoption of a new multi-tiered allocation policy in October 2018.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of the recent prioritization of patients on TMCS and reports of ECMO bridge-to-transplantation (BTT) mortality exceeding 30% at 1-year follow-up has made surgically implanted T-LVADs with and without T-RVADs an attractive clinical option for BTT patients. 1,3,6 The risk of mortality and device-related complications in patients on prolonged T-LVADs is exceedingly high necessitating either cardiac recovery, durable CF-LVAD implantation or OHT to avoid mortality. 8,9 The current evidence describing the outcomes following a direct bridge from T-LVADs to OHT is limited to small cohorts that include a variety of TMCS devices.…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients listed for an orthotopic heart transplant (OHT) has increased over the past decade due to the rising incidence of refractory heart failure as well as increased survival in patients supported with durable continuous-flow left ventricular assist devices (CF-LVADs). [1][2][3] Patients with CF-LVADs have superior waitlist survival and rates of transplantation when compared with patients supported with surgically implanted temporary left ventricular assist devices (T-LVAD), with and without temporary right ventricular assist devices (T-RVAD). 4,5 To create equitable access to donor organs for the highest mortality patients, the Organ Procurement and Transplantation Network in association with the United Network for Organ Sharing (UNOS) updated the cardiac transplant allocation system in October 2018.…”
Section: Introductionmentioning
confidence: 99%